2020
DOI: 10.29252/joge.4.3.68
|View full text |Cite
|
Sign up to set email alerts
|

Health related needs of the elderly in Sabzevar city of Iran , 2019

Abstract: Introduction: Elderly people often have complex and unknown needs but we have not yet fully recognized them in accordance with international standards in our country. Therefore, the present study attempts to more accurately identify the types of fulfilled or unmet needs related to the health of the elderly in Sabzevar city using valid and specialized tools. Methods: This descriptive cross-sectional study was performed on 240 elderly people over 60 years old without any cognitive problems in Sabzevar city in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Finally, nine studies 1 , 14 - 16 , 18 - 22 remained in the final analysis ( Figure 1 ). The total sample size was 2200 subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, nine studies 1 , 14 - 16 , 18 - 22 remained in the final analysis ( Figure 1 ). The total sample size was 2200 subjects.…”
Section: Resultsmentioning
confidence: 99%
“…In this dimension, eight studies 1 , 14 - 16 , 18 , 20 - 22 had indicated the percentage of met and unmet needs of the psychological dimension. The overall pooled proportion of psychological met needs was 23% (95% CI: 0.04-0.42), and the overall pooled proportion of unmet psychological needs was 0.04 (0.02, 0.05) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 51 ] In Iran, the lack of assessing the needs of the older people in the health care system is seriously threatening the older people status. [ 52 ]…”
Section: Discussionmentioning
confidence: 99%